Quality of life after coronary artery bypass grafting: a comparative study - Pistolas, Dimitrios; Papagiannaki, Vasileia; Diakomopoulou, Eleni; Argiriou, M; Ouzounidou, A; Apostolakis, Efstratios; Merkouris, Anastasios (My University, 2003)
The aim of this study was to assess the quality of life in elderly patients before and 4 months after coronary artery bypass graft (CABG) operation in order to identify areas for interventions and further improvement of the provided care. This is part of a bigger project to assess the quality of life in CABG patients over time. The collection of data was based on interviews by using the MACNE.W heart disease health-related quality of life questionnaire. The study sample consisted of 120 cardiac artery bypass surgery patients (CABS) (100 men, 20 women) with a mean Age of 63.13 years (±8.55) and an average length of stay 14.2 days (±4.78). There was a significant improvement of the physical (+1.79, P<0.001) and social (+1.57, P<0.001) state of the patients after the operation. The emotional state of the patients showed a very small improvement (+0.56, P=0,001) and the cognitive ability, as it was measured by three questions, showed a decline (-0.51, P<0.001). Patients, 4 months after the operation, exhibited a lower level of self-confidence and were more dependent on others. Sex, age, physical condition before the operation and chest pain were found to be related to the quality of life before and after the operation. The assessment of the quality of life has to be established as an official outcome indicator for the evaluation of therapeutic interventions of cardiac artery disease (CAD) patients. It is imperative that government plan and implement rehabilitation programs in order to cover the individual needs and enhance the quality of life of CABG patients.